Uncertainties in City Greenhouse Gas Inventories. (August 2015) - Wattenbach, Martin; Redweik, Richard; Lüdtke, Stefan; Kuster, Ben; Ross, Lutz; Barker, Alexandra; Nagel, Claus
Abstract: Cities worldwide are on the route to implement the Global Protocol for Community-Scale Greenhouse Gas Emission Inventories (GPC). However, many of these cities are already reporting or have reported their GHG emission in non GPC conform tools. We use a city heat cadaster integrated into an OGC CityGML 3D model to compare mapping schemes from the cCR by ICLEI, ECOSPEED Region and GPC. We demonstrate potential information losses and inconsistencies leading to potential uncertainties. In conclusion consistent data structures like CityGML are essential in order to use city GHG data for Monitoring, Reporting and Verification (MRV).